Cost Allocation Model In Construction Projects - Kartono Wibowo (International Conference on Coastal and Delta Areas, 2015)
Cost estimation is an important element in the overall cost management project, It is used to plan and control the resources, such as materials, labor, and equipment. In this case, the construction management has function to ensure the implementation of the construction project properly in order to achieve the goals of the project. Project planning urgently needs a precise and accurate method in analyzing the allocation of the proportion cost of the resources planned. It must be implemented in the beginning before start of the construction, therefore it is necessary to conduct a detail study of the factors related to the financial of the composition of resources such as labor, materials, and tools. Previous researches on cost allocation of construction project resources were carried out; Hermiati, Zahraie, B. and Tavakolan, M., Lin, K., Heon Jun, D. and El-Rayes. K. Hermiati. (2007) conducted a study about Modeling and Analysis of the wages of labor in the construction projects with the research objects of infrastructure development projects (building). Zahraie, B. and Tavakolan, M. (2009) examined the Stochastic Time-Cost-Resource Utilization Optimization (TCRO) Using Nondominated Sorting Genetic Algorithm and Discrete Fuzzy Sets). Lin, K. (2011) has conducted research on Human Resource Allocation for Remote Project Construction. Heon Jun, D. and El-Rayes, K. (2011) conducted research on Multi-objective Optimization of Resource Leveling and Allocation during Construction Scheduling. Previous researches on resource variable of project construction carried out by Muzayanah, et al. Muzayanah, et al (2008) modeled the proportion of project construction resources. The conclusion was in the form of a mathematical model of the proportion of project resources, and the average use of construction project resources. The conclusion was mathematical proportion of project resources and the average of construction project resources in a simple building compared to non-simple building. The conclusion of the first year study was project construction cost that has four variables; Wibowo, et al (2014), consisted of the cost variable of human resources, building material, equipment, and others cost. The final conclusion of this study (Wibowo, et al, 2015) resulted in a statistical/ mathematical model and conceptual framework model of the decision making system on the cost allocation of construction project. Statistical/ Mathematical Model of Cost Allocation on Project Construction in general